Patterns of planning and implementation of PJOK curriculum in elementary schools in the post-COVID-19 pandemic period - Mohammad Faruk; Mohammad Ali; Rudi Susilana; Laksmi Dewi; Norlidah Alias; I Made Sriundy M; Imam Syafi’i (Inovasi Kurikulum, 2024)
Learning planning must be adjusted to students’ conditions to achieve educational goals. The COVID-19 pandemic brought significant changes requiring high adaptability, especially in education. This study aims to identify planning and implementation patterns of the Physical Education and Health (PJOK) curriculum in elementary schools during the post-COVID-19 pandemic. Using a descriptive survey method, the research explored how PJOK teachers plan and implement home-based learning during this period. Data was collected via a Google Forms questionnaire from 33 PJOK teachers who participated in a Focus Group Discussion on post-pandemic curriculum planning. The study’s findings reveal that most teachers adjusted their planning based on the available facilities and infrastructure in students' homes. The curriculum was simplified to emphasize life skills relevant to the post-pandemic context. Implementing the PJOK curriculum requires collaboration with parents to monitor and support student learning at home. Teachers predominantly use WhatsApp to deliver instructional materials and rely on YouTube as a learning resource. This research highlights the need for adaptive curriculum strategies that accommodate challenges in post-pandemic education while ensuring effective learning despite limited resources. AbstrakPerencanaan pembelajaran harus menyesuaikan dengan kondisi siswa untuk mencapai tujuan pembelajaran. Pandemi COVID-19 menyebabkan perubahan lingkungan yang memerlukan adaptasi tinggi, terutama dalam pendidikan. Tujuan penelitian ini adalah untuk mengidentifikasi pola perencanaan dan implementasi kurikulum Pendidikan Jasmani dan Kesehatan di sekolah dasar pada masa pasca pandemi COVID-19. Metode yang digunakan adalah metode survei deskriptif untuk menggambarkan pola perencanaan yang dilakukan oleh guru Pendidikan Jasmani dan Kesehatan serta implementasi dalam pembelajaran di rumah pada masa pasca pandemi COVID-19. Instrumen yang digunakan adalah kuesioner yang diterapkan menggunakan google form kepada 33 guru Pendidikan Jasmani dan Kesehatan yang mengikuti Focus Group Discussion perencanaan kurikulum Pendidikan Jasmani dan Kesehatan di masa pasca pandemi COVID-19. Hasil penelitian ini menunjukkan bahwa sebagian besar guru Pendidikan Jasmani dan Kesehatan melakukan penyesuaian perencanaan berdasarkan kondisi sarana dan prasarana pendukung yang dimiliki orangtua. Penyederhanaan kurikulum yang berfokus pada kecakapan hidup peserta didik dalam situasi dan kondisi pasca pandemi COVID-19. Implementasi kurikulum PJOK di masa pasca pandemi COVID-19 membutuhkan kolaborasi dengan orang tua dalam proses penyampaian dan pemantauan kegiatan belajar siswa selama di rumah. Guru banyak menggunakan media aplikasi WhatsApp dalam menyampaikan informasi bahan ajar dan menggunakan YouTube sebagai sumber belajar.Kata Kunci: COVID-19; implementasi kurikulum; pendidikan jasmani dan kesehatan